Does government effectiveness and corruption control support political stability? - Nafis Dwi Kartiko (Komisi Pemberantasan Korupsi, 2024)
This study aims to investigate the relationship between government effectiveness, corruption control, and political stability. The data used is sourced from the World Competitiveness Yearbook provided by the Institute for Management Development. The analysis involves annual data collected regularly since 1987, covering a global sample of 66 countries for six years, from 2017 to 2022, with a total of 381 observations. Ordinary Least Squares (OLS) regression was used to investigate the research. The results confirm the importance of corruption control and government effectiveness in maintaining political stability. The analysis differentiates the effect of government effectiveness based on the quality of a country's political product, finding that improvements in government effectiveness are particularly important in improving political stability in countries with Low Political Product Quality. This signals that in countries with greater political and economic challenges, improvements in government effectiveness can have a significant impact on political stability.